ISLAMIC SOCIAL FINANCE ACCOUNTABILITY PRACTICE - Hani Werdi Apriyanti (IJIBE (International Journal of Islamic Business Ethics), 2017)
Islamic social finance, such as the zakat management Institution must guaranteee the accountability of the zakat management funds received from muzakki. The zakat management institution must understand the concept of accountability for islamic social finance institutions, in order to carry out the accountability process correctly. To guarantee the fulfilment of this accountability, The zakat management insitution needs to implement a good governance framework, zakat core prinsiple. This study aims to discuss the islamic accountability of islamic social finance in Indonesia, wether it is depend on the zakat core prinsiple or their own concept of accountability. This article is theoritical and conceptuaal study, with several method of collecting data from journal and direct observation. The result show that islamic social finance tend to providing financial and non financial information periodically to their stakeholders and public using  nformation Technology (IT) including social media (facebook, instans messaging, and the ohers) in a unique and simple way. They begin to change this fulfilment of accountability from traditionally to modern using the internet. However, there are still difficulties in implementing some aspect of zakat core principle because of the limited human resource. Therefore, it still necessary to developed ilsamic social finance system strategy with support and assistance on the implementation of accountability in islamic social finance in Indonesia.Keywords: accountability, islamic social finance, zakat core principle